Entrepreneurial Competencies And Business Performance In The Context Of Malaysian Young Agropreneur Programme - Ismail, Siti Zurianah (2019)
Agropreneurship has become a very important sector and can be considered as the backbone of economic development in Malaysia. The Young Agropreneur Programme introduced by the Ministry of Agriculture is part of the initiative to flourish the agropreneurship agenda.